1991
DOI: 10.1093/nar/19.7.1505
|View full text |Cite
|
Sign up to set email alerts
|

DNA hairpin loops in solution. Correlation between primary structure, thermostability and reactivity with single-strand-specific nuclease from mung bean

Abstract: Hairpin structures formed by seven DNA inverted repeats have been studied by PAGE, UV(CD)-spectroscopy and nuclease cleavage. The hairpins consisted of (CG)3 stems and loops of 2, 3 and 4 residues. Thermal stabilities (Tm) have been determined in low and high ionic strength buffers, where the hairpins were structured in the B- and Z-DNA form respectively. The thermodynamic parameters of hairpin formation have been obtained by a two-state analysis of the hairpin-coil transitions. It is found that, on increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 33 publications
4
31
0
1
Order By: Relevance
“…This prediction has been verified by previous studies showing that at least two single-strand-specific endonucleases, SI nuclease and mung bean nuclease (MBN), are capable of introducing nicks in the vicinity ofhairpin loops (23)(24)(25). However, all but one of the hairpins examined in those studies contained terminal loops with 3-8 non-complementary nucleotides.…”
Section: Introductionsupporting
confidence: 70%
“…This prediction has been verified by previous studies showing that at least two single-strand-specific endonucleases, SI nuclease and mung bean nuclease (MBN), are capable of introducing nicks in the vicinity ofhairpin loops (23)(24)(25). However, all but one of the hairpins examined in those studies contained terminal loops with 3-8 non-complementary nucleotides.…”
Section: Introductionsupporting
confidence: 70%
“…A DNA hairpin is made up of two parts: a base-paired stem and a single-stranded loop connecting the two halves of the stem. Structural studies have shown that the loop of fully complementary hairpins generally adopts a 2-or 4-unpaired-nucleotide structure, due to the tremendous steric constraints imposed by the bonding of the last two nucleotides (29,35,36). A DNA hairpin has therefore to be seen as a dynamic equilibrium adopting the more favorable energy conformation under a given steric stress.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors are involved in the counterbalance of stabilities of the loop and the stem regions and determine the predominant conformations of the hairpin (5,10). One very relevant factor is the effect of the base sequence of DNA hairpins on hairpin stability and loop folding (2,13,29,36). For example, Blommers et al have shown that the same hairpin will have a loop of 2 or 4 nucleotides upon a single nucleotide change in position N 1 (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, one, two, three, and four residue(s) of analogue X were planned to be incorporated into the loop moiety. The hexameric stem hairpin structure would be suitable for this study, because it is known to form stable hairpins with a loop consisting of two, three, or four thymidine residues (28). Thus, we designed the hairpinforming ODNs 5′-d[CGAACG-X n -CGTTCG]-3′ (I-1, n ) 1; I-2, n ) 2; I-3, n ) 3; I-4, n ) 4), shown in Figure 3, for this study.…”
Section: Resultsmentioning
confidence: 99%